Domain-specific risk-taking among finance professionals - Michael Razen; Michael Kirchler; Utz Weitzel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
Risk-assessment and risk-taking in various forms are among the most important tasks financial professionals face in their daily work. A large body of experimental studies has shown a substantial effect of the decision domain (gain vs loss domain) on risk-taking, predominantly among students. In a series of experiments set in different contextual frameworks, we investigate whether this domain effect is also present among experienced finance professionals and compare their decisions with people from the general population. Our results show that employees in the finance industry are equally prone to the domain effect in risk-taking than the general population. Interestingly, for domain-specific risk-taking in a finance context, we find that professionals are more reluctant to sell loser stocks than non-professionals.
Keywords: C91; C93; D81; G41; 330; Experimental Finance; Financial Professionals; Domain-specific risk-taking